Stylistic markers of pejorative vocabulary in Ukrainian-language cartoons - Babenko , Andriy (Current issues of Ukrainian linguistics: theory and practice, 2024)
The research is focused on the analysis of popular Ukrainian-language cartoons, such as "SpongeBob", "Cars", "Shrek", "The Adventures of Tom and Friends", "Speak Ukrainian", and "The Simpsons". The central goal of the study is to study how pejorative vocabulary in cartoons can influence the formation of children’s language skills and their worldview. An important component of our work is the analysis of different types of communication in animation and their potential impact on children’s perception through the principles of informatization, imitation and identification with characters. We seek to find out how animation, being not only a means of entertainment, but also an important element of artistic socialization, can shape children’s ideas about social norms, stereotypes and roles. Pejorative language, which often goes unnoticed by adults, can have a decisive impact on children’s development, contributing to the emergence of aggressive behavior patterns and the formation of negative stereotypes. In the context of our research, special attention is paid to cartoons, the speech of the characters of which contains pejorative vocabulary, which requires an in-depth analysis of their impact on children. In addition, the impact of globalization on the Ukrainian cartoon industry through the import of foreign cartoons, which carry cultural values and norms of behavior, often different from the traditions of the Ukrainian socio-cultural context, is considered. Such cartoons can influence the formation of the worldview of Ukrainian children, not always in a positive way. Therefore, our work also emphasizes the need to create high-quality domestic cartoon content that would correspond to national cultural traditions and values. The purpose of such content should be to promote the positive speech and emotional development of children, as well as to form in them an adequate understanding of social norms and values.